The role of color Duplex in diagnosing chronic cerebrospinal venous insufficiency in patients with multiple sclerosis - Khaled H. El Kaffas; Ahmed H.K. Abdelmaksoud; Amr Taha (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Introduction: CCSVI, has been recently hypothesized to play a role in the etiology of MS. It can be reliably assessed using Doppler sonography by evaluating the extra cerebral venous hemodynamics with changes in posture. Aim of study: To evaluate the prevalence of CCSVI in patients with MS. Patients and methods: A total of 60 patients were studied; (52) with relapsing–remitting MS, (4) with primary progressive MS and (4) with secondary progressive MS. Sixty healthy age and gender-matched controls were enrolled in this study. Patients were subjected to full clinical history, neurological examination and Doppler ultrasound assessment. Results: CCSVI defined as the presence of at least two positive venous hemodynamic criteria and was present in 8 of the 60 MS patients (13%) and was not found at any of the 60 controls (0%). Four patients showed the full 4 criteria for diagnosis while the other 4 patients only showed 2 criteria. CCSVI was noticed more to be frequent among SP and PP patients (25% and 25% respectively) in respect of RR MS (50%) and showing high significant value. Conclusion: We conclude that CCSVI is an unlikely cause of MS and it is likely to be a late secondary phenomenon.